2017
DOI: 10.2140/agt.2017.17.3779
|View full text |Cite
|
Sign up to set email alerts
|

On the integral cohomology ring of toric orbifolds and singular toric varieties

Abstract: We examine the integral cohomology rings of certain families of 2n-dimensional orbifolds X that are equipped with a well-behaved action of the n-dimensional real torus. These orbifolds arise from two distinct but closely related combinatorial sources, namely from characteristic pairs (Q, λ), where Q is a simple convex n-polytope and λ a labelling of its facets, and from ndimensional fans Σ. In the literature, they are referred as toric orbifolds and singular toric varieties respectively. Our first main result … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 16 publications
(17 reference statements)
0
42
0
Order By: Relevance
“…The aim of this section is to study the Poincaré polynomial of certain toric varieties. The main idea is to use a retraction sequence of a polytope introduced in [2,3,16]. We first begin by reviewing some facts on projective toric varieties associated with lattice polytopes and their properties which are necessary to our aim.…”
Section: Backgrounds: Polytopes and Projective Toric Varietiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this section is to study the Poincaré polynomial of certain toric varieties. The main idea is to use a retraction sequence of a polytope introduced in [2,3,16]. We first begin by reviewing some facts on projective toric varieties associated with lattice polytopes and their properties which are necessary to our aim.…”
Section: Backgrounds: Polytopes and Projective Toric Varietiesmentioning
confidence: 99%
“…Remark 2.3. Every simple polytope has at least one retraction sequence (see [3,Proposition 2.3]). However, some singular polytopes, for instance, the rhombododecahedron appeared in [15] do not admit a retraction sequence.…”
Section: Backgrounds: Polytopes and Projective Toric Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…which is called an orbifold lens space in [6]. We note that this orbifold L(Λ) has a natural T n -action.…”
Section: Torus Orbifolds Over σ∆ N−1mentioning
confidence: 99%
“…For toric manifolds the ring of piecewise polynomials on the fan is isomorphic to the face-ring of its quotient but this is not true for orbifolds in general. In [6] it is shown that the equivariant cohomology of projective toric orbifolds, under the condition of vanishing odd degree cohomology, can be realized as a subring of the usual face-ring of the fan that satisfies an intergrality condition.…”
Section: Introductionmentioning
confidence: 99%